Beyond identification of familial hypercholesterolemia: Improving downstream visits and treatments in a large health care system - Harin Lee; Tarun Kadaru; Ruth Schneider; Taylor Triana; Carol Tujardon; Colby Ayers; Mujeeb Basit; Zahid Ahmad; Amit Khera (American Journal of Preventive Cardiology)
Objective: Familial Hypercholesterolemia (FH) is underdiagnosed and undertreated. Several electronic health record (EHR) algorithms have been developed to improve identification of patients with FH. The approach to improving downstream processes of care and implementation of appropriate treatment after identification of these individuals is unclear. Methods: Individuals at UT Southwestern Medical Center with an LDL-C ≥ 190mg/dL (n = 8368) ever recorded in the EHR were included in an FH registry. As part of a QI program, random individuals from the registry deemed to possibly have FH were contacted via (1) MyChart message, (2) phone call, (3) letter, and/or (4) InBasket message to their PCP to notify them of the potential FH diagnosis, higher risk of ASCVD events, and offering referral to an FH specialist. Participants were contacted 1–4 times by one of these modalities. Chart extraction of contacted patients was performed to determine the type and frequency of contact and downstream visits and interventions. The composite primary outcome of the study included changes to lipid-lowering medications, family screening for FH, and new chart diagnosis of FH. Results: A total of 242 patients from the FH registry were reviewed of which 108 (mean age 55, 69 % women, highest mean LDL-C 267 ± 47 mg/dL) met the inclusion criteria. A total of 180 patient contact attempts were made (mean 1.7 per patient) with most being by MyChart (48 %) and telephone (41 %). Of those contacted, 35 % had a follow-up visit with a PCP and/or a lipid specialist, and 22 % saw any composite change. Patients whose PCP was contacted were more likely to have adjustments made to their lipid lowering medication(s) (p = 0.016), be diagnosed with FH (p = 0.025), and have a follow-up visit (p = 0.033). A greater number of contacts (2.17 vs 1.52, p < 0.001) was also associated with any composite change in outcome. Conclusions: Approximately 1 in 5 individuals in a large healthcare system who were contacted for a recorded LDL-C ≥ 190 mg/dL had a meaningful improvement in the management of severe hypercholesterolemia and diagnosis of FH. Various process factors were associated with a greater change in clinical care. These data highlight the importance of systematic evaluation to enhance interventions to improve the care of individuals with possible FH.